Management by scientific and technical development of Ukraine. Historical aspect (1920-1990) - L. M. Besov (History of science and technology, 2015)
Since the beginning of research institutes in the Soviet Union state planning existed. The researchers followed the creative intuition. Planning work is not touched their content and research results. The Soviet model of science began to be established since the late 1920s. The objects acknowledged planning topics and resources. The science and technology of development of Soviet Ukraine was accompanied by a strengthening of the influence of the centralized state. Ukraine Scientists have achieved outstanding scientific and technological results and won the world championship in some priority areas of the Soviet state. His work has become attractive for young people with dignity and evaluated. Since the beginning of the 1970 s. Scientific-technical programs. They predicted join forces artists such programs. In the Soviet Union enforced 200-Union research programs. One program funded 20-30 ministries and departments. Financing of the ministries has hampered the implementation of programs. In 180 of them institutes of the Academy of Sciences of Ukraine performed research for machine building, steel industry, coal industry, instrumentation, chemical and food and so on. industries republic. In 1980-ies. Created interbranch scientific and technical complexes. The main instrument for managing their activities became the only research plan and implement research programs.